What do we know about complex-contrast training? A systematic scoping review - Thapa, R. K.; Weldon, A.; Freitas, T. T.; Boullosa, D.; Afonso, J.; Granacher, U.; Ramirez-Campillo, R. (Sports Medicine - Open, 2024)
Background The complex-contrast training (CCT) method utilizes two exercises with different loads and movement velocities in a set-by-set fashion to induce multiple neuromuscular adaptations. The speculated primary mechanism involves the post-activation potentiation or post-activation performance enhancement (PAPE) of the muscles used during the heavy load (low velocity) exercise, thereby improving the performance of lower load (high velocity) exercise. However, no previous study has attempted to systematically synthesize the available evidence on CCT (e.g., if post-activation potentiation or PAPE was measured during the training sessions during the intervention period). This study aimed to synthesize the available evidence on CCT using a systematic scoping review approach. More specifically, we identified gaps in the literature using an evidence gap map (EGM), and provided future directions for research.